Development of Creativity and Business Innovation in Furniture Making Using SCAMPER Technique - Wijaya, Heny Ardiyanti; Alam, Syamsu; Halim, Nur (Universitas Negeri Makassar, 2024)
This study aims to explore the development of creativity and business innovation in furniture making using the SCAMPER technique in Manongkoki Village, enabling furniture entrepreneurs to enhance their creativity and innovation in business development. The research method employed is qualitative descriptive research, with data collection methods including observation, interviews, and documentation of the research subjects. The development of creativity and business innovation in furniture making using the SCAMPER technique is highly effective for furniture entrepreneurs as it helps generate new creative ideas and introduce innovations that can enhance product value and meet the evolving market demands. Additionally, the SCAMPER technique can be applied in various fields since each element of SCAMPER is not limited to a specific aspect, making it versatile for use in any area.